Influence of the companion's support during labor in a hospital in Huancayo - Carrillo Cayllahua , Mirian (2022)
Objective: To determine the influence of the companion's support during labor at the Hospital Regional Docente Materno Infantil El Carmen. Material and Methods: Substantive, retrospective, descriptive, correlational, prospective cross-sectional study, with a population of 362 pregnant women in labor, from which the sample was obtained through inclusion and exclusion criteria, obtaining a sample of 98 pregnant women in labor, for the measurement of the variables the technique of observation and documentary analysis was used. Results: 42.9% were primigravida and 57.1% were multigestational, and of the total number of deliveries attended, 61.2% were with an attendant and 38.8% without; of the deliveries with an attendant, the most frequent relationship was the couple with 52.0%, followed by the mother with 6.1%, others (father, brother, friends) with 2.0% and finally the sister with 1.0%. Conclusions: Family accompaniment during labor favors maternal benefits in all its dimensions; in relation to perinatal benefits, it only favors fetal heart rate and does not benefit the other dimensions studied with a significance level of 0.05.